Experimental Study of a Variable Stiffness Seat Suspension Installed With a Compact Rotary MR Damper - Sun, Shuaishuai; Yang, Jian; Wang, Penghui; Nakano, Masami; Shen, Longjiang; Zhang, Shiwu; Li, Weihua (Frontiers in Materials, 2021)
Traditional MR seat suspension without stiffness control is not able to avoid the resonance between the excitation and the seat though it can damp the vibration energy. To solve this problem, this paper proposed a variable stiffness (VS) magnetorheological (MR) damper to implement an advanced seat suspension. Its natural frequency can be shifted away from the excitation frequency through the variations of stiffness, thereby realizing the non-resonance control. The new seat suspension is designed and prototyped firstly and then its dynamic property under different energizing current, excitation amplitude and excitation frequency was tested using an MTS machine. The testing results verified its stiffness controllability. The vibration attenuation performance of the seat suspension was also evaluated on a vibration shaking table. The vibration reduction performance of the seat suspension was evaluated under two kinds of excitations, i.e. harmonic excitation and random excitation; the experimental results indicate that the new seat suspension outperforms passive seat suspensions regarding their ride comfort.